Comparison of ExPress Implantation and Partial Deep Sclerectomy Combined with ExPress Implantation and Simultaneous Phacoemulsification. (28th November 2019) - Frączkiewicz-Skok, Marietta; Konopińska, Joanna; Mariak, Zofia; Rękas, Marek
Abstract : Background . To compare the effectiveness and safety profile of ExPress implantation versus partial deep sclerectomy combined with ExPress implantation and simultaneous phacoemulsification. Patients and Methods . A prospective, randomized control study with 24-month follow-up was performed. 114 eyes were included, of which 42 eyes underwent phacoemulsification with simultaneous implantation of the Ex-Press device (ExPress), and deep sclerectomy with phacoemulsification and simultaneous implantation of the Ex-Press device (DS-ExPress) was performed in 72 eyes. The main outcome measures were intraocular pressure (IOP), corrected distance visual acuity (CDVA), the number of antiglaucoma medications, and the rate of complications. Surgical success was defined as complete (without antiglaucoma medications) with IOP ≤18 mmHg in criterion A, IOP ≤16 mmHg in criterion B, and IOP ≤12 mmHg in criterion C. Satisfactory success was defined as the same IOP levels for individual criteria with a maximum of 2 antiglaucoma medications. Results . Before the procedure, mean IOP in the ExPress group was 17.5 ± 4.7 mmHg; after 24 months, it decreased by 13% to 16.0 ± 3.0 mmHg (P < 0.05 ). In the DS-ExPress group, mean IOP reduced from 16.3 ± 4.4 mmHg to 14.3 ± 3.3 mmHg (P < 0.05 ), which was a 9% reduction compared to the initial value. In the DS-ExPress group, 65.9% of the patients did not use topical pharmacotherapy, and the same is true for 29.2% of the ExPress group (P = 0.004 ). Conclusions . This modification is efficient in surgical treatment of glaucoma, especially when very low postoperative IOP is needed. A less amount of antiglaucoma medicines are needed.